Atomic‐Level Pt Electrocatalyst Synthesized via Iced Photochemical Method for Hydrogen Evolution Reaction with High Efficiency. Issue 33 (24th July 2022) - Sun, Zhiyi; Yang, Yuqi; Fang, Chaohe; Yao, Yinchao; Qin, Fengjuan; Gu, Hongfei; Liu, Qingqing; Xu, Wenjing; Tang, Hao; Jiang, Zheng; Ge, Binghui; Chen, Wenxing; et al.
Abstract: In heterogeneous catalysis, metal particle morphology and size can influence markedly the activity. It is of great significance to rationally design and control the synthesis of Pt at the atomic level to demonstrate the structure‐activity relationship toward electrocatalysis. Herein, a powerful strategy is reported to synthesize graphene‐supported platinum‐based electrocatalyst, that is, nanocatalysts with controllable size can be prepared by iced photochemical method, including single atoms (Pt‐SA@HG), nanoclusters (Pt‐Clu@HG), and nanocrystalline (Pt‐Nc@HG). The Pt‐SA@HG exhibits unexpected electrocatalytic hydrogen evolution reaction (HER) performances with 13 mV overpotential at 10 mA cm −2 current densities which surpass Pt‐Clu@HG and Pt‐Nc@HG. The in situ X‐ray absorption fine structure spectroscopy (XAFS) and density functional theory (DFT) calculations determine the Pt‐C3 active site is linchpin to the excellent HER performance of Pt‐SA@HG. Compared with the traditional Pt‐Nx coordination structure, the pure carbon coordinated Pt‐C3 site is more favorable for HER. This work opens up a new way to adjust the metal particle size and catalytic performance of graphene at a multiscale level. Abstract : In heterogeneous catalysis, metal particle morphology and size can influence markedly the activity. Rational design and controllable synthesis of Pt at the atomic level is of great significance to demonstrate the structure‐activity relationship toward electrocatalysis. Herein, a powerful strategy is reported to synthesize graphene‐supported Platinum‐based electrocatalyst, including single atoms, nanoclusters, and nanocrystalline.